Ancestral Heritage Languages As Mechanisms Of Resistance: The Case Of Limonese Creole In Costa Rica (Revista Rupturas, 2023)
The coloniality processes that took place around the world have damaged values and principles of ancestral heritage, including linguistic practices since hegemonic forms have been imposed on the beliefs and worldviews of minority communities. Fortunately, struggles by indigenous and Afro-descendant communities have constituted forms of resistance against these hegemonic forces. We refer to the case of the English-based creole language spoken by the Afro-Limonese community in Costa Rica, Limonese Creole. Based on data obtained through qualitative methodologies, we find that, despite the hegemonic power exercised by the Spanish and English languages over this vernacular language and its evident weakening, Limonese Creole still forms an essential part of the Afro-Limonese identity.
Keywords: decoloniality; resistance; minority languages; Limonense Creol